Relationship between Cardiometabolic index and endometriosis in a US nationally representative sample: results from NHANES 1999-2006 - Jiarui Hou; Wenting Chen; Rui Wang; Xuchun Huang; Xuchun Huang; Xiaojing Cao; Xiaojing Cao; Xiaoyun Wang; Xiaoyun Wang (Frontiers in Endocrinology)
BackgroundEndometriosis is an estrogen-dependent gynecological endocrine condition and a systemic inflammatory disease associated to improper lipid metabolism and increased cardiovascular risk. The Cardiometabolic Index (CMI) is a novel indicator representing visceral adipose tissue distribution and metabolic dysfunction, integrating lipid metabolism indicators and the waist-to-height ratio. While anomalies in lipid metabolism are often associated with (BMI) Body Mass Index, literature consistently shows a negative link between endometriosis and female BMI, and some studies have found that endometriosis is one of the few reproductive diseases not persistently positively correlated with obesity. Given the limitations of BMI, a comprehensive index like CMI is crucial for exploring the incidence of endometriosis. Currently, research on the correlation between CMI and endometriosis is lacking, prompting this study to investigate this association.ObjectiveTo investigate the association between the CMI and the risk of having endometriosis in a sample representing the entire U.S. population.Study designA cross-sectional analysis was conducted using data from four cycles of the National Health and Nutrition Examination Survey (NHANES) spanning the years 1999 to 2006. The study included individuals aged 20 to 54 with a documented history of endometriosis and complete CMI data. Logistic regression analysis, subgroup and interaction analyses, smooth curve fitting, and restricted cubic splines (RCS) were utilized to examine the association between CMI and endometriosis.ResultsThe study found that individuals with higher CMI had an increased probability of developing endometriosis. This relationship remained significant after adjusting for potential confounders such as age, ethnicity, Poverty Income Ratio (PIR), drinking, smoking, education level, and marital status. The fully adjusted model revealed a positive correlation between CMI and endometriosis (OR = 1.21; 95% CI, 1.04–1.40, p < 0.05). Subgroup and interaction analyses showed no significant effect modification by age, BMI, PIR, hypertension, drinking, smoking, or menarche age (all p-values for interaction > 0.05).ConclusionOur study shows a link between CMI and the chance of getting endometriosis.Due to the common occurrence of endometriosis and the lack of clarity surrounding their cause, more study is needed to confirm our results and find out if CMI could be used as a warning sign for endometriosis.